Monitoring astrocyte calcium microdomains with improved membrane targeted GCaMP reporters - SHIGETOMI, EIJI (2010)
Astrocytes are involved in synaptic and cerebrovascular regulation in the brain. These functions are regulated by intracellular calcium signalling that is thought to reflect a form of astrocyte excitability. In a recent study, we reported modification of the genetically encoded calcium indicator (GECI) GCaMP2 with a membrane-tethering domain, Lck, to generate Lck-GCaMP2. This GECI allowed us to detect novel microdomain calcium signals. The microdomains were random and ‘spotty’ in nature. In order to detect such signals more reliably, in the present study we further modified Lck-GCaMP2 to carry three mutations in the GCaMP2 moiety (M153K, T203V within EGFP and N60D in the CaM domain) to generate Lck-GCaMP3. We directly compared Lck-GCaMP2 and Lck-GCaMP3 by assessing their ability to monitor several types of astrocyte calcium signals with a focus on spotty microdomains. Our data show that Lck-GCaMP3 is between two- and four-times better than Lck-GCaMP2 in terms of its basal fluorescence intensity, signal-to-noise and its ability to detect microdomains. The use of Lck-GCaMP3 thus represents a significantly improved way to monitor astrocyte calcium signals, including microdomains, and will facilitate detailed exploration of their molecular mechanisms and physiological roles.